Injection molding of micro devices - Tan, Kayne Keng'An. (2011)
Injection molding represents a critical process for manufacturing plastic parts. A major contribution of this process is its capability to manufacture complex geometries in one production step of an automated process. Often, injection molded parts can be found in daily life: automotive parts, household articles, consumer electronics goods and toys. In this project, the optimized parameters of two polymers for injection molding were being studied. The two polymers are Polymethyl Methacrylate grade LG2 (PMMA LG2) and Cyclic Olefin Copolymer grade 8007 (COC 8007) supplied by Sumitomo Chemical Co., Ltd. Methacrylates Division and TOPAS® (Thermoplastic Olefin Polymer of Amorphous Structure) respectively.The main objective of this report is to optimize the molding parameters for the injection molding process of micro devices using PMMA LG2 and COC 8007. To achieve it, a trial Design of Experiment (DOE) experiment from Minitab was performed on six factors, namely Injection Pressure, Injection Speed, Mold Temperature, Barrel Temperature, Holding Pressure and Holding Time. From there, the author identified 3 critical factors which demonstrated greater impact on the molded process for both materials and performed full factorial experiments on them. The 3 determining factors for PMMA LG2 were injection pressure, mold temperature and holding pressure. For COC 8007, the 3 determining factors were injection pressure, mold temperature and barrel temperature.